Design and application of electron energy measurement system based on silicon photodiode - Jianghai Geng; Xinyu Wang; Fangcheng Lv; Shengfu Wang; Ping Wang; Yujian Ding (AIP Advances, 2020)
The change in electron energy is the key to ionization. Studying the change law plays an important role in analyzing the gap discharge process. In this paper, an electron energy measurement system is designed based on a silicon photodiode, and the feasibility analysis is given. Combined with a photomultiplier tube, the electron energy of a slightly uneven field of a 3 cm ball-to-plate gap under dc voltage is obtained during the discharge process. This system can obtain the relationship curve between external voltage and electron energy, which provides help in analyzing the development of the discharge process and the establishment of the criteria.